Advanced information systems engineering workshops : CAiSE 2020 International Workshops, Grenoble, France, June 8-12, 2020, Proceedings /: CAiSE 2020 International Workshops, Grenoble, France, June 8-12, 2020, Proceedings. (2020) - Unknown
No abstract available